Penghayatan Nilai-Nilai Islam (Kredo) dan Self Concept Remaja pada Siswa Kelas VII SMP Muhammadiyah 2 Yogyakarta) - Aulia, Fitri (AL-TAZKIAH, 2013)
Adolescent is phase transitions between stages of children with the adult stage. Adolescent is a unique individual learning and prone to learning disorders experienced since the phase transition. Self-concept is a discussion that influence birth of learning disorders. Then the formation of a positive self concept being seriously considered for the part of the private childbirth emotionally mature, intellectually, and socially. Appreciation of the values of Islam are termed Creed values human cherished beliefs, which led him in thought and action, because every human being is required to make smart decisions in the form of planning, implementation, assessment, and riskassessment and acceptance of any decision responsible. Formulation of the problem in this study, (1) How does self concept on adolescent self?, (2) How is appreciation of the values of Islam (creed) teens teens self concept formed?. The research method used was qualitative. The conclusion is, adolecent have a building that is very prone to self concept, considering the number of changesexperienced, both in terms of boilogis (ripening hormone-hormone in his body), emotional and cognitive (as the effect of changes in her hormone). The low self-concept creed on the subject, very easily influenced by factors outside themselves, such as school, family, and social environment, which resulted in high and low self concept owned, and influence the decision making process in itself.